Development of Coronavirus Disease 2019 Surveillance, Prevention and Control Using Bubble and Seal Model in Factory, Maha Sarakham Province - ภูริบัญชา แพรพรรณ; มงคลสินธุ์ เชิดพงษ์; จังภูเขียว ปวีณา (Journal of Health Science of Thailand, 2022)
The objectives of this research were to study of context and problems of corona disease 2019 in a factory, and develop a model for surveillance, prevention and control using bubble and seal approach, as well as to evaluate the outcomes. It was conducted as a participatory research at a chicken processing factory in Maha Sarakham province applying PAOR components: Planning (P), Action (A), Observation (O) and Reflection (R). Selected samples were 22 government officials and factory leaders as well as 100 employees from the factory. Data were collected through in-depth interviews using a set of questionnaires to assess knowledge and preventive behavior associated with COVID-19; and the data were analyzed using content analysis, descriptive statistics, percentage, mean, standard deviation and paired t-test statistic. As for the results, this study had developed a model of COVID-19 surveillance, prevention and control in a bubble-and-seal manner consisting of policies and measures to drive operation under the provincial communicable disease committee with participation from government agencies and the workplaces. Staff leaders were trained in the factory using participatory decision-making techniques with clear communication guidelines and evaluation through local network participation. After applying the model, it was found that the coverage of the second dose COVID-19 vaccination in employees were 95.6%, the average score of knowledge and preventive behavior of COVID-19 was significantly increased (p<0.001); and the COVID-19 outbreak was under controlled within 14 days. The key success factors of this model implementation were local network participation, continuous communication about COVID-19 outbreak, and the regularly control using bubble and seal measures.